“Globally Local” CSR in MNC’s : how MNC’s balance the pressures for global integration and local responsiveness in their CSR strategy? - Teixeira, Amanda Crasto Correia de Freitas (2019)
This research aims to advance the discussion of how multinational companies balance global integration with local responsiveness in their corporate social responsibility (CSR) strategy. In particular, it studies the mechanisms between home and host countries in the development and implementation processes of a transnational CSR strategy and the types of monitoring mechanisms used. Structured by a qualitative study with a case study on a hospitality group, we find that the transnational approach is the most suitable indeed to guarantee a good balance between global standardization and local reactiveness. We advocate so by proposing some key mechanisms of a transnational CSR strategy that allow for this balance, and we discuss the main tensions and solutions that arise from this strategy. Finally, we suggest that the transnational approach to CSR should not be untied to local and global approaches and that the integration of the three is what makes the transnational approach the most suitable for MNC’s that want to balance global integration with local responsiveness.